Aspirin Attenuates Hyperoxia-Induced Acute Respiratory Distress Syndrome (ARDS) by Suppressing Pulmonary Inflammation via the NF-κB Signaling Pathway - Tung, Yu-Tang; Wei, Chi-Hsuan; Yen, Chih-Ching; Lee, Po-Ying; Ware, Lorraine B.; Huang, Hao-En; Chen, Wei; Chen, Chuan-Mu (Frontiers in Pharmacology, 2022)
Acute respiratory distress syndrome (ARDS) is a common destructive syndrome with high morbidity and mortality rates. Currently, few effective therapeutic interventions for ARDS are available. Clinical trials have shown that the effectiveness of aspirin is inconsistent. The contribution of platelets to the inflammatory response leading to the development of ARDS is increasingly recognized. The antiplatelet agent aspirin reportedly exerts a protective effect on acid- and hyperoxia-induced lung injury in murine models. Our previous study showed that pretreatment with aspirin exerts protective effects on hyperoxia-induced lung injury in mice. However, the mechanisms and therapeutic efficacy of aspirin in the posttreatment of hyperoxia-induced acute lung injury (ALI) remain unclear. In this study, we used a homozygous NF-κB-luciferase+/+ transgenic mouse model and treated mice with low-dose (25 μg/g) or high-dose (50 μg/g) aspirin at 0, 24, and 48 h after exposure to hyperoxia (inspired oxygen fraction (FiO2) > 95%). Hyperoxia-induced lung injury significantly increased the activation of NF-κB in the lung and increased the levels of macrophages infiltrating the lung and reactive oxygen species (ROS), increased the HO-1, NF-κB, TNF-α, IL-1β, and IL-4 protein levels, and reduced the CC10, SPC, eNOS, Nrp-1, and IκBα protein levels in the lung tissue. Pulmonary edema and alveolar infiltration of neutrophils were also observed in the lung tissue of mice exposed to hyperoxia. However, in vivo imaging revealed that posttreatment with aspirin reduced luciferase expression, suggesting that aspirin might reduce NF-κB activation. Posttreatment with aspirin also reduced hyperoxia-induced increases in the numbers of lung macrophages, intracellular ROS levels, and the expression of TNF-α, IL-1β, and IL-4; it also increased CC10, SPC and Nrp-1 levels compared with hyperoxia exposure alone. Lung histopathology also indicated that the aspirin posttreatment significantly reduced neutrophil infiltration and lung edema compared with hyperoxia exposure alone. Aspirin effectively induces an anti-inflammatory response in a model of hyperoxia-induced lung injury. Thus, aspirin may have potential as a novel treatment for hyperoxia-induced ALI.